Etnobotani Indigofera di Indonesia - Muzzazinah, Muzzazinah (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Tom-toman (Indigofera),Â  plants introduced but become an important for the batik and weavers community in Indonesia. This study aims to explore information ofÂ  Indigofera. Most people use tom as natural dyes. Most people in Flores and Sumba were utilized as a livestock sheep, sheep, and cattle. People in Pamekasan using leaf tom (I. tinctoria) as a herbal medicine for children are difficult to eat (cekok).